Implementation of Special Village Financial Assistance Policy to Realizing Village Self Reliance in Rapak Lambur Village - Hanapi Hanapi; Musmuliadi Musmuliadi; Agustinus Djiu (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The village plays a central role in Indonesia's decentralized governance and serves as a strategic unit for achieving equitable and sustainable development. In this context, the Special Village Financial Assistance (BKKD/K) policy was introduced as a mechanism to enhance financial capacity, promote local autonomy, and stimulate grassroots development initiatives. This study explores the implementation of the BKKD/K policy in Rapak Lambur Village, Tenggarong District, Kutai Kartanegara Regency, with the objective of assessing its effectiveness in fostering village self-reliance. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and analysis of official documents. The research highlights that BKKD/K has contributed significantly to infrastructure improvements, economic empowerment programs, and increased village-generated income. However, the implementation process faces several persistent challenges, including limited financial management capacity among village officials, inadequate community participation in planning and monitoring, and weak accountability mechanisms. Findings suggest that while the BKKD/K policy has the potential to reduce dependency on central government transfers, its success depends largely on good governance practices such as transparency, accountability, and participatory decision-making. Moreover, enhancing the managerial skills of village apparatus and promoting civic engagement are critical to ensuring sustainable outcomes. The study underlines the importance of adaptive policy support and technical assistance to overcome institutional constraints and to align village development priorities with community needs. Ultimately, the implementation of BKKD/K in Rapak Lambur demonstrates both the promise and the limitations of fiscal decentralization at the village level, offering practical insights for policymakers and practitioners aiming to strengthen village autonomy and resilience across Indonesia.